Finding social need-les in a haystack: ascertaining social needs of Medicare patients recorded in the notes of care managers - Paul R. Shafer; Amanda Davis; Jack A. Clark (BMC, 2023)
Abstract Background Unmet social needs may impair health and access to health care, and intervening on these holds particular promise in high-risk patient populations, such as those with multiple chronic conditions. Our objective was to identify social needs in a patient population at significant risk-Medicare enrollees with multiple chronic illnesses enrolled in care management services-and measure their prevalence prior to any systematic screening. Methods We partnered with Renova Health, an independent Medicare Chronic Care Management (CCM) provider with patients in 10 states during our study period (January 2017 through August 2020). Our data included over 3,000 Medicare CCM patients, representing nearly 20,000 encounters. We used a dictionary-based natural language processing approach to ascertain the prevalence of six domains of barriers to care (food insecurity, housing instability, utility hardship) and unmet social needs (health care affordability, need for supportive services, transportation) in notes taken during telephonic Medicare CCM patient encounters. Results Barriers to care, specifically need for supportive services (2.4%) and health care affordability (0.8%), were the most prevalent domains identified. Transportation as a barrier to care came up relatively less frequently in CCM encounters (0.1%). Unmet social needs were identified at a comparatively lower rate, with potential housing instability (0.3%) flagged most followed by potential utility hardship (0.2%) and food insecurity (0.1%). Conclusions There is substantial untapped opportunity to systematically screen for social determinants of health and unmet social needs in care management.